Tyrosinase Inhibitor Activity Measurement of Crude and Purified Extract of Moringa Leaves (Moringa oleifera L.) - Zainal Abidin; Ummu Khaeriah; Zuhrina Zuhrina; Mamat Pratama; Muzakkir Baits (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Moringa leaves is one of the plants that have antioxidant activity. The compounds that have strong antioxidant activity also have strong antityrosinase activity. Moringa leaves contain flavonoid compounds that can inhibit tyrosinase activity in the melanin formation process. This study aimed to determine tyrosinase inhibitor activity of crude and purified extract of moringa leaves (Moringa oleifera L.). Tyrosinase inhibitory activity measurement was done by in vitro studies with measuring dopachrome from the oxidation of L-tyrosine in the mechanism of melanogenesis. The crude extract obtained by use maceration extraction method and ethanol solvent, whereas the purified extract obtained by use liquid-liquid extraction method and ethyl acetate solvent. The results showed that hydroquinone has IC50 value of 18,234 μg/mL while crude extract of moringa leaves shows IC50 value of 4405,24 μg/mL and purified extract of moringa leaves shows IC50 value of 401,6228 µg/mL. Purified extract of moringa leaves more active as tyrosinase inhibitor than its crude extract but less active than hydroquinone.Keywords: Moringa leaves, Purified extract, Tyrosinase Inhibitor, UV Rays